TECHNOLOGICAL CHALLENGES IN THE CONTEXT OF TRAINING MODERN LAWYERS - Andreanova, Inna; Rozhkova, Anna; Bulgakova, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The development of modern technologies poses new challenges for training legal professionals. Traditional forms of teaching do not produce the desired secondary effect (for example, the students' interest in acquiring knowledge in a particular course) or the end result (acquiring the competences needed for the modern job market). Consequently, teaching should be more focused on the application of new, non-traditional forms of education while preserving the best traditions of legal training (handwriting rather than e-device, developing communication skills and emotional intelligence). As a result, this article analyses the use of technologies and potential threats they pose to maintaining traditional values specific to the legal profession in the education process. The article, using the method of literature analysis, dialectical research, the deductive and inductive method, analysis and synthesis, and modelling, which ensures the validity of the results obtained, sociological observation method, including  as well as the experience of Rezekne Academy of Technologies and of Pskov State University in the training of new lawyers, summarises information and draws conclusions on how to use technology and its development opportunities in the education process.